Duodenal hematoma following endoscopic duodenal biopsy in an adult requiring arterial embolization and surgical evacuation: a case report and review of the literature - Buchanan, Kelly L.; Wilechansky, Robert M.; Pathipati, Mythili P.; Goldstein, Allan M.; Ryan, Daniel P.; Yarze, Joseph C. (Frontiers in Gastroenterology, 2024)
A 21-year-old man presented with severe abdominal pain four days after undergoing upper endoscopy with duodenal biopsies and was found to have an intramural duodenal hematoma. Symptoms progressed after attempts at diet advancement, and repeat imaging showed an enlarging hematoma with duodenal obstruction. The patient was managed with arterial embolization followed by laparoscopic surgical evacuation of the hematoma. This is the first report of an enlarging duodenal hematoma managed by this combination approach. While surgical interventions have previously been reserved for the most severe cases, we review the literature on minimally invasive approaches to manage this rare endoscopic complication.